Stenting in the Treatment of Acute Ischemic Stroke: Literature Review - Samaniego, Edgar A.; Dabus, Guilherme; Linfante, Italo (Frontiers in Neurology, 2011)
Recanalization of acute large artery occlusions is a strong predictor of good outcome. The development of thrombectomy devices resulted in a significant improvement in recanalization rates compared to thrombolytics alone. However, clinical trials and registries with these thrombectomy devices in acute ischemic stroke (AIS) have shown recanalization rates in the range of 40-81%. The last decade has seen the development of nickel titanium self-expandable stents (SES). These stents, in contrast to balloon-mounted stents, allow better navigability and deployment in tortuous vessels and therefore are optimal for the cerebral circulation. SES were initially used for stent-assisted coil embolization of intracranial aneurysms and for treatment of intracranial stenosis. However, a few authors have recently reported feasibility of deployment of SES in AIS. The use of these devices yielded higher recanalization rates compared to traditional thrombectomy devices. Encouraged by these results, retrievable SES systems have been recently used in AIS. These devices offer the advantage of resheathing and retrieving of the stent even after full deployment. Some of these stents can also be detached in case permanent stent placement is needed. Retrievable SES are being used in Europe and currently tested in clinical trials in the United States. We review the recent literature in the use of stents for the treatment of AIS secondary to large vessel occlusion.